Free-Radical Scavenging and In Vitro Anticancer Assay of Indonesian Black Garlic with Different Time Processing - Riyadi, Sandra Amalia; Vanawati, Noviana; Farah, Harra Ismi; Hafizah, Aulia UI; Hasanah, Uswatun; Herlina, Eka (Universitas Pendidikan Mandalika, 2025)
The process of producing Black Garlic (BG) in Indonesia has not used a standard method and the right dosage. BG is produced through termal processing, compared with fresh garlic (FG) there are obvious changes in color, taste, and biological activities. BG was produced by different time of heating. Several studies have shown that BG has several pharmacological activities including antioxidants and anticancer. The aim of this research is to determine the optimal produced of BG to assess the potential antioxidant and anticancer activity. FG was heated at high temperature 60-70ºC with 85-95% humidity without any additives for various period of time which is 30, 40, 50, 60 days. Ethanol (EtOH) extract of BG 30; 40; 50 and 60 days and FG as a control were partionate with n-hexane, ethyl acetate (EtOAc), n-buthanol (n-BuOH), and water then evaporated in 40 °C. Each extract of FG and BG were tested Free-radical scavenging and anticancer activity. Free-radical scavenging was determined by 1,1 diphenyl-2-picrylhydrazyl (DPPH) method, and cytotoxicity of crude extract was tested by 3-(4,5-dimethylthiazol-2-yl)—2,5-diphenyltetrazolium bromide (MTT) assay against MCF-7 human breast cancer cell line. The result demonstrated that BG exhibited significantly enhanced radical scavenging activity compared to FG across different aging periods. Notably, EtOAc and n-hexane fractions obtained after 30, 40, and 60 days of thermal aging showed strong antioxidant activity with IC₅₀ values below 50 µg/mL. Importantly, this study demonstrates that a defined thermal aging duration of 30 days, combined with EtOAc fractionation, yields the most potent antioxidant fraction and the lowest IC₅₀ value (47.27 µg/mL) against MCF-7 cells, indicating that thermal aging time is a key determinant governing the antioxidant and anticancer potency of BG. These findings provide novel evidence linking controlled thermal aging parameters to the optimization of BG bioactivity, thereby offering a robust scientific basis for standardized BG processing with enhanced functional and therapeutic potential.